Wake-induced vibrations of iced pin joint hangers of suspension bridges based on wind tunnel test and new method of transiting test. (August 2021) - Li, Shengli; Li, Qing; Guo, Pan; Liu, Xin; Wang, Dongwei; Wang, Xidong
Abstract: The wind-induced vibration of suspension bridge hangers may be due to hanger icing. This study presents a new test method named transiting test method, combining with the section model wind tunnel test, to investigate the wake-induced vibrations of iced pin joint hangers under limited conditions. Results reveal that according to wind tunnel test and DenHartog galloping theory, the attack angle of 3° is the angle at which the wake galloping of iced pin joint hangers is most likely to occur. The driving wind field is stable in the transiting test and exhibits relatively minimal interference from the external factors under limited conditions. The predominant frequencies of vehicular vibration in the transiting test exhibit no marked relation with the fundamental frequency of the model, thereby demonstrating transiting test can satisfy the requirements of wind-resistant research on iced pin joint hangers. The wake galloping-reduced wind speed of iced pin joint hangers with D-shaped ice and a 30 mm icing thickness is 165, and the leeward iced hanger is vulnerable to endurance failure. The wake galloping critical wind speed of pin joint hangers with icing is lower than that without icing. The findings have important implications for the wind-resistance of suspension bridges with pin joint hangers.